Pengembangan Sistem Informasi Manajemen Administrasi dan Keuangan Berbasis Web Jemaat HKBP Palmarum Tarutung - Ardiles Sinaga; Ana Muliyana; Oppir Hutapea (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The HKBP Palmarum Church faces significant challenges in its administration and financial management, which have been conducted manually. This approach exposes the system to risks of data loss, delays in information updates, and a lack of transparency in financial reporting. This community service project aims to develop a web-based management information system to address these issues. The methodology employed is the Software Development Life Cycle (SDLC) with a prototyping approach. The outcome of the project includes a system capable of managing congregation data, finances, and service information digitally. With the implementation of this system, church services are expected to become more efficient, transparent, and serve as a model for other churches.